Candida-related lesions dalam rongga mulut: diagnosis dan strategi penatalaksanaanya - Firstine Kelsi Hartanto; Krysta Yosvara (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Candida–related lesions can present as denture sore mouth intraorally and cheilitis angular extra orally. Some predisposing factors include ill-fitting dentures, malnutrition, and poor oral hygiene. Objective: To determine the proper diagnosis and management of sore mouth dentures and cheilitis angular in patients with ill-fitting dentures and bad oral hygiene. Case report: A 59-year-old male patient presented with a burning sensation on the hard palate and sores at the corners of the lips, which were aggravated by the meal and opening of the mouth. No history of systemic diseases was found. Extra-orally erythema fissure lesions were found surrounded by multiple white areas at the corners of the lips bilaterally and were painful. Intra-oral examination showed erythema macular lesions that extend to the gingiva and palate mucosa that contact the denture base. Nystatin oral suspension combined with fluconazole, and multivitamins as supportive therapy. Educational suggestions such as the replacement of dentures and improve oral hygiene conditions were given. Conclusion: Denture sore mouth and cheilitis angular in this case are caused by Candida albicans related to the insufficient denture and poor oral hygiene. Management for this case by providing causative treatment with single or combine antifungal drugs along with proper communication, instructions, and education regarding the diseases.